2009
DOI: 10.1007/s00296-009-0960-1
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Kawasaki syndrome followed by systemic onset-juvenile idiopathic arthritis mimicking Kawasaki syndrome

Abstract: A 3-month-old child was first treated for incomplete Kawasaki syndrome with three cycles of intravenous immunoglobulins and aspirin, then with methylprednisolone which led to fever remission. The same child was re-hospitalized after a 10-month-period of well-being for the suspicion of a new episode of Kawasaki syndrome, which appeared to be immunoglobulin-resistant: extensive testing failed to provide an alternative diagnosis of any infectious or infiltrative disease. Diagnosis of systemic onset-juvenile idiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In the pre‐IVIG era, early‐onset polyarthritis was more common; it developed during the first 10 days of illness and tended to involve multiple joints, including small and large weight‐bearing joints . This type of arthritis is often undistinguishable from systemic juvenile idiopathic arthritis . Late‐onset arthritis (sub‐acute stage) occurs after the 10th day of illness and is mainly oligoarticular, involving large weight‐bearing joints .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pre‐IVIG era, early‐onset polyarthritis was more common; it developed during the first 10 days of illness and tended to involve multiple joints, including small and large weight‐bearing joints . This type of arthritis is often undistinguishable from systemic juvenile idiopathic arthritis . Late‐onset arthritis (sub‐acute stage) occurs after the 10th day of illness and is mainly oligoarticular, involving large weight‐bearing joints .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that arthritis in KD might lead to a worse outcome because it indicates a more intense inflammatory response, accounting for some of the first‐line therapy resistance . However, Gong et al .…”
Section: Discussionmentioning
confidence: 99%
“…Arthritis or arthralgia complicates up to one‐third of KD patients and has been divided into two types 1–3 . Early onset arthritis, which develops during the first 10 days of illness, affects both small and large joints and is often indistinguishable from systemic juvenile idiopathic arthritis (JIA) 3,4 . Late‐onset arthritis, which develops on the 10th day or later of illness, primarily affects weight‐bearing joints, similar to oligoarticular JIA, and lasts for 6–8 weeks 2–6 .…”
mentioning
confidence: 99%
“…Though extremely rare, an ascending aortic aneurysm with extensive anterior myocardial infarction and a large pseudoaneurysm of the LDA requiring a coronary arterial bypass were, respectively, described in a 12-and 16-year-old patient with Behçet's disease [24,25]. Also, systemic-onset juvenile idiopathic arthritis with or without macrophage activation can mimic an incomplete KS and show coronary artery dilatation, which should erroneously lean toward KS diagnosis [26][27][28].…”
Section: Discussionmentioning
confidence: 99%